Fighting Pathogenic Bacteria on Two Fronts: Phages and Antibiotics as Combined Strategy - Tagliaferri, Thaysa Leite; Jansen, Mathias; Horz, Hans-Peter (Frontiers in Cellular and Infection Microbiology, 2019)
With the emerging threat of infections caused by multidrug resistant bacteria, phages have been reconsidered as an alternative for treating infections caused by tenacious pathogens. However, instead of replacing antibiotics, the combination of both types of antimicrobials can be superior over the use of single agents. Enhanced bacterial suppression, more efficient penetration into biofilms, and lowered chances for the emergence of phage resistance are the likely advantages of the combined strategy. While a number of studies have provided experimental evidence in support of this concept, negative interference between phages and antibiotics have been reported as well. Neutral effects have also been observed, but in those cases, combined approaches may still be important for at least hampering the development of resistance. In any case, the choice of phage type and antibiotic as well as their mixing ratios must be given careful consideration when deciding for a dual antibacterial approach. The most frequently tested bacterium for a combined antibacterial treatment has been Pseudomonas aeruginosa, but encouraging results have also been reported for Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Enterococcus faecalis, and Burkholderia cepacia. Given the immense play area of conceivable phage-antibiotic combinations and their potential excess value, it is time to recapitulate of what has been achieved so far. This review therefore gathers and compares the results from most relevant studies in order to help researchers and clinicians in their strategies to combat multidrug resistant bacteria. Special attention is given to the selected bacterial model organisms, the phage families and genera employed, and the experimental design and evaluation (e.g., in vitro vs. in vivo models, biofilm vs. planktonic culture experiments, order and frequency of administration etc.). The presented data may serve as a framework for directed further experimental approaches to ultimately achieve a resolute challenge of multidrug resistant bacteria based on traditional antibiotics and phages.